Targeting insulin‐like growth factor 2 mRNA‐binding protein 1 (IGF2BP1) in metastatic melanoma to increase efficacy of BRAFV600E inhibitors. Issue 5 (5th February 2018) - Kim, TaeWon; Havighurst, Thomas; Kim, KyungMann; Albertini, Mark; Xu, Yaohui G.; Spiegelman, Vladimir S.
Abstract : Melanoma is one of the deadliest forms of skin cancer. Although BRAF inhibitors significantly enhance survival of metastatic melanoma patients, most patients relapse after less than a year of treatment. We previously reported that mRNA binding protein Insulin‐like growth factor 2 mRNA‐binding protein 1 (IGF2BP1) is overexpressed in metastatic melanoma and that expression of IGF2BP1 confers resistance to chemotherapeutic agents. Here we demonstrate that IGF2BP1 plays an important role in the sensitivity of melanoma to targeted therapy. Inhibition of IGF2BP1 enhances the effects of BRAF‐inhibitor and BRAF‐MEK inhibitors in BRAF V600E melanoma. Also, knockdown of IGF2BP1 alone is sufficient to reduce tumorigenic characteristics in vemurafenib‐resistant melanoma. These findings suggest that IGF2BP1 can be a novel therapeutic target for melanoma.